Digitalisasi Bumdes Optimalisasi Company Profile Dan Sistem Pemesanan Unit Usaha Bumdes Bagjawaluya - Ai Ilah Warnilah; Yanti Apriyani; Yani Sri Mulyani; Muhammad Dhafa Alfareza; Vincent Christian (STMIK Royal, 2025)
Abstract: The village of Sumberjaya has considerable local economic potential through the management of the Bagjawaluya Village-Owned Enterprise (BumDes), particularly in the Mini Soccer, Campground, Kiosk Rental, Water Supply, and Village Internet business units. However, limitations in the use of digital technology and promotional media have resulted in low effectiveness of services to the community. This community service activity aims to support the optimization of company profile creation and online booking systems for existing business units at BumDes Bagjawaluya. The target partners in this activity are BumDes managers, with 15 participants involved. To measure the effectiveness of the activity, an evaluation method consisting of a pre-test and post-test was used to assess the increase in participants' understanding, as well as a questionnaire to explore their perceptions and readiness to adopt digital technology. The results of the activity showed an increase in understanding of company profile management by 86.67% and business unit ordering applications by 93.33%. These results indicate that the community service activity had a positive impact on improving the digital literacy of BumDes managers. Keyword: BumDes; Company Profile; Digitalization; Ordering; Optimization Abstrak: Desa Sumberjaya memiliki potensi ekonomi lokal yang cukup besar melalui pengelolaan Badan Usaha Milik Desa (BumDes) Bagjawaluya, khususnya pada unit usaha Mini Soccer, Bumi Perkemahan,Sewa Kios, Air weslik, Internet Desa. Namun, keterbatasan dalam pemanfaatan teknologi digital dan media promosi menyebabkan rendahnya efektivitas layanan kepada masyarakat. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mendukung optimalisasi pembuatan company profile, dan sistem pemesanan online untuk unit usaha yang ada pada BumDes Bagjawaluya. Mitra sasaran dalam kegiatan ini adalah pengelola BumDes dengan jumlah peserta yang terlibat sebanyak 15 orang. Untuk mengukur efektivitas kegiatan, digunakan metode evaluasi berupa pre-test dan post-test untuk menilai peningkatan pemahaman peserta, serta kuisioner untuk menggali persepsi dan kesiapan mereka dalam mengadopsi teknologi digital. Hasil kegiatan menunjukkan peningkatan pemahaman untuk pengelolaan Company Profile 86,67%, aplikasi pemesanan unit usaha 93,33%. .Hasil ini menunjukkan bahwa kegiatan pengabdian memberikan dampak positif terhadap peningkatan literasi digital pengelola BumDes. Kata Kunci: BumDes; Company Profile; Digitalisasi; Pemesanan; Optimalisasi